Investigating The Level of State Anxiety Among Newly Enrolled Undergraduate Female Nursing Students in Karachi, Pakistan - Ahmed, Farhan; Ali, Yasir; Malik, Anwar Ali; Rubina; Khan, Ameer Ullah (Indus Journal of Bioscience Research, 2024)
Background: Anxiety is an emotional state that opposes the possibility of encountering potentially unpleasant future circumstances. Objective: To assess the level of state anxiety among newly enrolled undergraduate female nursing students. Methods: A descriptive cross-sectional study was conducted at a public female nursing institute in Karachi, Pakistan from January to April 2024. The sample size was 225, calculated by using Open Epi with 95% confidence interval. A convenient sampling technique was used. All newly enrolled undergraduate female nursing students were included while the other classes’ students were excluded from the study. The 20 item Spielberger State Anxiety Inventory questionnaire was used to assess the level of state anxiety. Approval of the study was obtained from the concerned institute. Written consents were taken from the participants, background and questionnaire were well explained to the participants. Statistical Package for Social Sciences (SPSS) Version 26 was used for data analysis. Results: The level of anxiety was high (83.6%) among participating students, (13.8%) of the students observed with moderate level of anxiety and only (2.7%) of the students recorded no or low level of anxiety. There was a statistically significant difference found between the mean scores of father’s occupation and education level. Conclusion: The decline in mental health during nursing education demonstrated the need of interventions for reducing their stress, anxiety, and depression. All faculty members must offer students one-on-one counselling services and to give them practical stress management techniques.